Targeted alpha-particle therapy: imaging, dosimetry, and radiation protection. (October 2018) - Lassmann, M.; Eberlein, U.
Systemic or locoregionally administered alpha-particle emitters are highly potent therapeutic agents used in oncology that are fundamentally novel in their mechanism and, most likely, overcome radiation resistance as the alpha particles emitted have a short range and a high linear energy transfer. The use of alpha emitters in a clinic environment requires extra measures with respect to imaging, dosimetry, and radiation protection. This is shown for the example of 223 Ra dichloride therapy. After intravenous injection, 223 Ra leaves the blood and is taken up rapidly in bone and bone metastases; it is mainly excreted via the intestinal tract. 223 Ra can be imaged in patients with a gamma camera. Dosimetry shows that, after a series of six treatments for a 70-kg person with an overall administered activity of 23 MBq, 223 Ra results in an absorbed alpha dose of approximately 17 Gy to the bone endosteum and approximately 1.7 Gy to the red bone marrow. During administration, special care must be taken to ensure that no spill is present on the skin of either the patient or staff. Due to the low dose rate, the treatment is normally performed on an outpatient basis; the patient and carers should receive written instructions about the therapy and radiation protection.